1976
DOI: 10.1080/01621459.1976.10480982
|View full text |Cite
|
Sign up to set email alerts
|

Moments of the Range of Samples from Nonnormal Populations

Abstract: The probability density function for the range of a sample from a population whose distribution can be represented by an Edgeworth series is developed. Moments of the range are obtained and the numerical values of the corrective functions arising due to nonnormality tabulated. Results for moments of the range of various nonnormal distributions are compared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Samples are simulated from eight symmetric distributions with kurtoses (β 2 ) from 2.00 to 6.48. Singh (1976) found that kurtosis is the distribution parameter that affects the sampling distribution of the mean range. Thus, in this article, we study symmetric distributions of varying kurtosis but not skewness to determine the effect of distribution shape on the standardized mean range.…”
Section: Distributionsmentioning
confidence: 99%
“…Samples are simulated from eight symmetric distributions with kurtoses (β 2 ) from 2.00 to 6.48. Singh (1976) found that kurtosis is the distribution parameter that affects the sampling distribution of the mean range. Thus, in this article, we study symmetric distributions of varying kurtosis but not skewness to determine the effect of distribution shape on the standardized mean range.…”
Section: Distributionsmentioning
confidence: 99%